Assessment and modeling of oxygen tension in porous structures and engineered tissue constructs - Gerard, Nathanael Adrianus (2013)
Tissue Engineering holds the promise to repair damaged human tissues and organs by engineering tissues in the laboratory. Usually, cells are seeded in porous scaffolds and subjected to a bioreactor for the regeneration of tissues. Unfortunately, the regenerated tissues commonly suffer from inadequate thickness and cell density. They are usually non-homogenous, thicker near the periphery but less dense near the bottom [1]. These problems make the tissue grown this way unsuitable for clinical applications. It is believed that this is due to limited diffusion of essential nutrients (most importantly oxygen) into the scaffold, which hampers tissue growth. We hypothesized that the scaffold’s structural properties, such as void fraction, pore size distribution, degree of cross-linking influence the ability of oxygen diffusion in the scaffold. Thus, it is necessary to study oxygen diffusion profiles in scaffolds in order to design better scaffolds to enhance cellular activities and tissue quality. [4th Award]